2013
DOI: 10.1093/occmed/kqt003
|View full text |Cite
|
Sign up to set email alerts
|

Work-related post-traumatic stress disorder

Abstract: ResultsProfessionals such as police officers, firefighters and ambulance personnel often experience incidents that satisfy the stressor criterion for the PTSD diagnosis. Other professional groups such as health care professionals, train drivers, divers, journalists, sailors and employees in bank, post offices or in stores may also be subjected to work-related traumatic events. Work-related PTSD usually diminishes with time.Conclusions Mental health problems prior to the traumatic event and weak social support … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
188
1
12

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(209 citation statements)
references
References 65 publications
8
188
1
12
Order By: Relevance
“…This finding may be due to the fact that rescue divers expect to experience such events and that they are taken care of and have a good debriefing system. It is known that prevention of work-related post-traumatic stress disorder includes a sound organisational and psychosocial work environment, systematic training of employees, social support from colleagues and managers and a proper follow-up of employees after a critical event [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…This finding may be due to the fact that rescue divers expect to experience such events and that they are taken care of and have a good debriefing system. It is known that prevention of work-related post-traumatic stress disorder includes a sound organisational and psychosocial work environment, systematic training of employees, social support from colleagues and managers and a proper follow-up of employees after a critical event [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…대상자의 일반적 특성으로는 선행 연구 결과를 토대로 외상 후 스 트레스 장애 발생에 영향을 미치는 요인으로 고려될 수 있는 성별 [2,6], 연령 [6,17], 교육수준 [17], 결혼상태 [10], 직무 관련 특성으로 는 근무형태 [10], 현재 맡은 업무(과학수사관, 검시조사관) [2,6], 총 근무경력 [9,10], 현재 업무 수행기간 [1,2], 지난 한달 간 사건현장으 로 출동한 횟수 [8,9], 정신건강서비스 이용 여부 [16,17] PTSD=post traumatic stress disorder. PTSD=post traumatic stress disorder.…”
Section: ) 대상자 특성unclassified
“…army, police, firefighters, etc.) are at a high risk of experiencing traumatic events and research indicates that the prevalence of PTSD among this population lies between 7.5 and 25% (Berger et al, 2012; Impact, 2008; Skogstad et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Skogstad et al (2013) found indications that personnel trained to deal with stressful situations were at a lower risk of PTSD, thus a preventative training to prepare how to effectively cope with life stressors seems especially relevant for individuals in professions with a high risk of experiencing traumatic events. Several technology-supported resilience trainings have been investigated in previous studies, including predeployment stress inoculation training (Hourani, Kizakevich, & Hubal, 2011), stress resilience in virtual environments (Rizzo et al, 2011), immersion and practice of arousal control training (Bouchard, Bernier, Boivin, Morin, & Robillard, 2012) and the stress resilience training system (Cohn, Weltman, Ratwani, Chartrand, & McCraty, 2010) (for a review see Favié, Vakili, Brinkman, Morina, & Neerincx, 2016).…”
Section: Introductionmentioning
confidence: 99%